Comparison of properties of raw pulse flours with those of jet-cooked, drum-dried flours. (October 2018) - Felker, Frederick C.; Kenar, James A.; Byars, Jeffrey A.; Singh, Mukti; Liu, Sean X.
Abstract: The properties of whole bean flours of navy, pinto, and black beans and chickpeas were compared with those of flours that had been passed through a steam jet cooker and drum dried. Analysis of structure, particle size, color, solubility, pasting characteristics, dietary fiber, oligosaccharides, and protein digestibility revealed differences from raw flours with potential advantages for food applications, including increased soluble fiber on average from 53 to 62 g/kg. Hot water solubility increased from 10 to 37 g/100 g, while particle size, water absorption index, and viscosity after pasting were decreased. Color changes in the flours suggested solubilization and redistribution of seed coat pigments. The treatments increased extractability of raffinose family oligosaccharides from 34 to 37 mg g −1 . Starch granules were dissolved during jet-cooking, and the dried product consisted of a uniform composite matrix. These results revealed changes in the physicochemical and functional properties of bean flours with the potential to increase the utilization of pulse flours in foods. Highlights: Cooked and dispersed starch granules formed a composite matrix on drying. Treatments decreased particle size, water absorption index, and viscosity after pasting. Treatments increased soluble fiber and extractability of raffinose saccharides. Color changes suggested partial extraction and redistribution of pigments.